2016
DOI: 10.1111/bju.13409
|View full text |Cite
|
Sign up to set email alerts
|

Do stones still kill? An analysis of death from stone disease 1999–2013 in England and Wales

Abstract: ObjectivesTo analyse the trends in the number of deaths attributable to urolithiasis in England and Wales over the past 15 years (1999-2013). Urolithiasis has an estimated lifetime risk of 12% in males and 6% in females and is not perceived as a life-threatening pathology. Admissions with urinary calculi contribute to 0.5% of all inpatient hospital stays, and the number of deaths attributable to stone disease has yet to be identified and presented. Materials and MethodsOffice of National Statistics data relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 24 publications
0
40
0
2
Order By: Relevance
“…Study cohort in Japan reported that increased BMI was associated with the risk of kidney stones. The risk of kidney stone formation was much higher in people with BMI 23.8-35.6 kg/ m 2 compared with people with BMI 15.9-21.6 kg/m (Kum et al, 2016;Yoshimura et al, 2016). A cohort study in the United States in postmenopausal women also suggests that increased BMI is associated with kidney stones (p<0,001) (Sorensen et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Study cohort in Japan reported that increased BMI was associated with the risk of kidney stones. The risk of kidney stone formation was much higher in people with BMI 23.8-35.6 kg/ m 2 compared with people with BMI 15.9-21.6 kg/m (Kum et al, 2016;Yoshimura et al, 2016). A cohort study in the United States in postmenopausal women also suggests that increased BMI is associated with kidney stones (p<0,001) (Sorensen et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
“…Endokrinologi Indonesia, 2015; Kum et al, 2016). Measurement of fasting blood was taken after the respondent fast for at least 8 hours and maximum 14 hours and only allowed to drink fresh water.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations